We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
124
2
avatar

What is (f⋅g)(x)?

f(x)=x^2+2x−6

g(x)=x^4+3

 

 

What is (f−g)(x)?

 

f(x)=x^3−2x^2+12x−6

g(x)=4x^2−6x+4

 May 17, 2019
 #1
avatar+8778 
+3

What is  (f ⋅ g)(x) ?

f(x)  =  x2 + 2x - 6

g(x)  =  x4 + 3

 

(f ⋅ g)(x)  =  f(x) g(x)         Substitute  (x2 + 2x - 6)  in for  f(x)  and substitute  (x4 + 3)  in for  g(x)

 

(f ⋅ g)(x)  = (x2 + 2x - 6) (x4 + 3)

 

(f ⋅ g)(x)  = (x2 + 2x - 6)(x4 + 3)

 

If you need to, you can expand the right side of the equation.

 May 17, 2019
 #2
avatar+8778 
+3

What is  (f - g)(x) ?

f(x)  =  x3 - 2x2 + 12x - 6

g(x)  4x2 - 6x + 4

 

(f - g)(x)  =  f(x) - g(x)         Substitute  (x3 - 2x2 + 12x - 6)  in for  f(x)  and substitute  (4x2 - 6x + 4)  in for  g(x)

 

(f - g)(x)  =  (x3 - 2x2 + 12x - 6) - (4x2 - 6x + 4)

 

(f - g)(x)  =  (x3 - 2x2 + 12x - 6) - (4x2 - 6x + 4)

 

If you need to, you can simplify this by distributing the -1 outside the parenthesees and combining like terms.

 May 17, 2019

29 Online Users

avatar
avatar
avatar